The Aggregate Impact of Investment, Inflation, Labor, Exports, and Internet Users on the Income of the Creative Industry Subsector of Application and Game Developers in Indonesia. - hendri hermawan; Dwi Wulandari (Dinamis : Journal of Islamic Management and Bussiness, 2025)
This research aims to analyze the influence of investment, inflation, number of workers, export value, and number of internet users on the income of the creative application and game developer industry subsector in Indonesia. The data population used in this research is the creative industry subsector of Application and Game Developers in Indonesia in 2011-2015. The analysis method used is the multiple regression analysis method with the EViews program. The results of the research show that investment, number of workers, export value and number of internet users have a significant influence on the income of the creative application and game developer industry subsector in Indonesia, while inflation does not have a significant influence on the income of the creative application and game developer industry subsector in Indonesia . subsector of the creative application industry and game developers in Indonesia.